French braid [large type] - Tyler, Anne (Random House Large Print, 2022)
"The Garretts take their first and last family vacation in the summer of 1959. They hardly ever venture beyond Baltimore, but in some ways they have never been farther apart. Mercy has trouble resisting the siren call of her aspirations to be a painter, which means less time keeping house for her husband Robin. Their teenage daughters, steady Alice and boy-crazy Lily, could not have less in common. Their youngest, David, is already intent on escaping his family's orbit, for reasons none of them understands. Yet as these lives advance across decades, the Garretts' influence on one another ripples unmistakably through each generation, much like French-braided hair keeps its waves even after it is undone. Full of heartbreak and hilarity, French Braid is classic Anne Tyler: a stirring, uncannily insightful novel of tremendous warmth and humor that illuminates the kindnesses and cruelties of our daily lives, the impossibility of breaking free from those who love us, and how close--yet how unknowable--every family is to itself"--